2020
DOI: 10.33828/sei.v31.i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Flipping The Use of Science-Technology and Society Issues as Triggering Students' Motivation and Chemical Literacy

Abstract: The aim of this paper was to investigate the effect of the use of science, technology, and society (STS) issues through flipped and traditional learning environments on students' motivation to learn chemistry as well as their chemical literacy (CL). Two freshman engineering classes totaling 89 students taught by the same instructor enrolled in a general chemistry course at a university were the sample of the study. The study had one intervention and one comparison group (CG); the groups were randomly assigned.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…After answering and being assessed, the scores obtained by each student were categorized into the high, moderate, and low categories. The used of the context-based approach is better to increase students' chemical literacy level (Cigdemoglu, 2020). There are several phenomena that we often encounter in everyday life that are closely related to chemistry and are also related to science in formal education.…”
Section: Resultsmentioning
confidence: 99%
“…After answering and being assessed, the scores obtained by each student were categorized into the high, moderate, and low categories. The used of the context-based approach is better to increase students' chemical literacy level (Cigdemoglu, 2020). There are several phenomena that we often encounter in everyday life that are closely related to chemistry and are also related to science in formal education.…”
Section: Resultsmentioning
confidence: 99%
“…Several modules were developed using a method approach, such as intertextual, contextual, socio-scientific issues, and so on [8][9][10][11][12][13][14]. This method is applied as a basis for compiling the module's content, which is expected to have an impact on students' chemical literacy.…”
Section: Icmscementioning
confidence: 99%
“…Outside the Philippines, there have been review papers and empirical evidence demonstrating the positive outcomes of STS education among students; studies have suggested that STS can increase science literacy and critical thinking (Mulyanti et al, 2020;Yapıcıoğlu & Kaptan, 2017), foster changes in scientific attitudes such as suspension of belief and challenging authority (Çalik & Karatas, 2019), enhance science motivation (Cigdemoglu, 2020), promote the use of moral judgments on socio-scientific issues (Yapıcıoğlu & Kaptan, 2017), sociopolitical awareness and engagement (Chowdhury et al, 2020) and even develop soft skills such as communication, interpersonal skills, and professionalism (Roswita et al, 2021).…”
Section: The Relevance Of Sts Educationmentioning
confidence: 99%